Intestinal fungi and antifungal secretory immunoglobulin A in Crohn’s disease - Sun, Meng; Ju, Jingyi; Xu, Hongzhen; Wang, Yufang (Frontiers in Immunology, 2023)
The human gastrointestinal tract harbors trillions of commensal microorganisms. Emerging evidence points to a possible link between intestinal fungal dysbiosis and antifungal mucosal immunity in inflammatory bowel disease, especially in Crohn’s disease (CD). As a protective factor for the gut mucosa, secretory immunoglobulin A (SIgA) prevents bacteria from invading the intestinal epithelium and maintains a healthy microbiota community. In recent years, the roles of antifungal SIgA antibodies in mucosal immunity, including the regulation of intestinal immunity binding to hyphae-associated virulence factors, are becoming increasingly recognized. Here we review the current knowledge on intestinal fungal dysbiosis and antifungal mucosal immunity in healthy individuals and in patients with CD, discuss the factors governing antifungal SIgA responses in the intestinal mucosa in the latter group, and highlight potential antifungal vaccines targeting SIgA to prevent CD.